Supervision of financial planning companies in consumer protection efforts - Sylvana Murni Deborah Hutabarat; Siti Nurul Intan Sari Dalimunthe; Wardani Rizkianti; Muthia Sakti (Universitas Muhammadiyah Magelang, 2023)
Buying and selling transactions, both services and goods, are growing rapidly along with technological developments. The profession of financial planning has been in great demand by the public in recent times, but this is inseparable from the existence of disputes which result in losses for consumers. Misappropriation of authority and violations committed by financial planning companies violate consumer rights. The Financial Services Authority has also yet to supervise because financial planners are not included in the financial sector. This research examined legal protection for financial planning consumers through supervision based on safety, certainty, and benefit principles. A statutory approach supports the normative juridical method and uses secondary data. The results of the study show that legal protection for consumers of financial planning companies is based on Article 10 letter c of Law Number 8 of 1999 on Consumer Protection, Articles 103 and Article 104 of Law Number 8 of 1995 on Capital Markets, Article 28 of Law Number 19 of 2016 on ITE, Article 378 and Article 372 of the Criminal Code and Article 1365 of the Civil Code.